The Influence of Store Atmosphere and Social Media Marketing on Purchase Decisions through Prices at the Unnathi Pakubuwono Beauty Clinic Jakarta - Fitria, Abelina Dini; Sijabat, Rosdiana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The study’s purpose is to investigate the impact of Store’s Atmosphere and Social Media Marketing (SMM) to Purchase Decision through Price at The Unnathi Pakubuwono Jakarta beauty clinic. Survey was done by sharing online questionnaires. The target population were all the customers of the beauty clinic that use their service/bought any product at least once in the last 3 months. There were 30 samples used for pre-test and 310 samples for the final test. Questionnaires’ results then analysed using PLS-SEM method with SmartPLS 3.0 software. Results shows that Store Atmosphere positively impacts Purchase Decision, Store Atmosphere also positively impacts Price. Store Atmosphere and SMM both positively impact Price. Price positively impacts Purchase Decision. Price is has positive mediating effect in both how Store Atmosphere affect Purchase Decision and how SMM affect Purchase Decision with the former being stronger. Based on that result, it is expected that The Unnathi Pakubuwono Jakarta as a beauty clinic will invest in making a better store atmosphere, better SMM and adjust the price accordingly so that purchase decision will be increased.